2022
DOI: 10.1002/ajmg.b.32918
|View full text |Cite
|
Sign up to set email alerts
|

ADHD‐associated PARK2 copy number variants: A pilot study on gene expression and effects of supplementary deprivation in patient‐derived cell lines

Abstract: Recent studies show an association of Parkin RBR E3 ubiquitin protein ligase (PARK2) copy number variations (CNVs) with attention deficit hyperactivity disorder (ADHD). The aim of our pilot study to investigate gene expression associated with PARK2 CNVs in human‐derived cellular models. We investigated gene expression in fibroblasts, hiPSC and dopaminergic neurons (DNs) of ADHD PARK2 deletion and duplication carriers by qRT PCR compared with healthy and ADHD cell lines without PARK2 CNVs. The selected 10 genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…Two of these studies are our own work, using hiPSC-derived dopaminergic neurons to investigate metabolic differences in ADHD patient carriers of parkin (PARK2) copy number variables. We found changes in PARK2 gene and protein expression, ATP production and basal oxygen consumption rate in CNV carriers 26 , along with altered transcriptomics 27 . A recent study by Yde Ohki et al was able to identify proliferation rate alterations in hiPSC-derived neural stem cells derived from male child and adolescent ADHD patients 28 .…”
Section: Introductionmentioning
confidence: 78%
“…Two of these studies are our own work, using hiPSC-derived dopaminergic neurons to investigate metabolic differences in ADHD patient carriers of parkin (PARK2) copy number variables. We found changes in PARK2 gene and protein expression, ATP production and basal oxygen consumption rate in CNV carriers 26 , along with altered transcriptomics 27 . A recent study by Yde Ohki et al was able to identify proliferation rate alterations in hiPSC-derived neural stem cells derived from male child and adolescent ADHD patients 28 .…”
Section: Introductionmentioning
confidence: 78%
“…In one case, a 230 Kb duplication of 6q26 was identified that included the PARK2 gene. CNVs in this gene have been reported as a risk factor for ADHD [ 36 ]. The finding was maternally inherited and, as such, was classified as a VUS.…”
Section: Discussionmentioning
confidence: 99%
“…Both may be a result of long-lasting alterations in neurodevelopmental processes, but may also be one of the etiopathogenic factors. Partially linked with mitochondrial dysfunction, the energy metabolism imbalance in ADHD has been discussed as a possible source of neurodevelopmental delays ( Cannon Homaei et al, 2022 ; Foschiera et al, 2022 ; Radtke et al, 2022 ). Cerebral glucose hypometabolism has been found in childhood-onset adult ADHD patients ( Zametkin et al, 1990 ), however, this may also be a consequence of deficits in impulse control leading to metabolic syndrome ( di Girolamo et al, 2022 ).…”
Section: Attention-deficit Hyperactivity Disorder Current Genetic And...mentioning
confidence: 99%